The post-Soviet "Orient" in stories by Vladimir Makanin and Liudmila Petrushevskaia. Issue 1 (3rd April 2017) - Anisimova, Irina
ABSTRACT: This article analyzes a paradoxical feature in post-Soviet Russian literature and film, where an anti-imperial message coexists with colonial tropes. It focuses on two short stories: "Slabye kosti" ("Weak Bones, " 1988) by Liudmila Petrushevskaia and "Kavkazskii plennyi" ("Prisoner of the Caucasus, " 1995) by Vladimir Makanin. Set respectively in Central Asia and the Caucasus, these stories reflect on the troubled Russian and Soviet relationship with these regions. Despite their artistic complexity and anti-imperial messages, these works are trapped by the literary tropes and cultural stereotypes of the past. These stories relate to a broader cultural trend characteristic of post-Soviet Russian culture. On the one hand, Russian culture has remained unreceptive to post-colonial discourses adopted by Western intellectuals. On the other hand, the resurgence of imperial preoccupations in contemporary Russia, as well as the anxiety surrounding Russia's territorial integrity, preclude the development of Russia's own discourses on ethnically distinct peripheries and identities. As a result of this discursive silence, even nuanced writers, such as Makanin and Petrushevskaia, rely on the traditional models of representing the Caucasus and Central Asia.